Regioselective N-alkylation of the 1H-indazole scaffold; ring substituent and N-alkylating reagent effects on regioisomeric distribution - Alam, Ryan M.; Keating, John J. (Beilstein Journal of Organic Chemistry, 2021)
The indazole scaffold represents a promising pharmacophore, commonly incorporated in a variety of therapeutic drugs. Although indazole-containing drugs are frequently marketed as the corresponding N-alkyl 1H- or 2H-indazole derivative, the efficient synthesis and isolation of the desired N-1 or N-2 alkylindazole regioisomer can often be challenging and adversely affect product yield. Thus, as part of a broader study focusing on the synthesis of bioactive indazole derivatives, we aimed to develop a regioselective protocol for the synthesis of N-1 alkylindazoles. Initial screening of various conditions revealed that the combination of sodium hydride (NaH) in tetrahydrofuran (THF) (in the presence of an alkyl bromide), represented a promising system for N-1 selective indazole alkylation. For example, among fourteen C-3 substituted indazoles examined, we observed > 99% N-1 regioselectivity for 3-carboxymethyl, 3-tert-butyl, 3-COMe, and 3-carboxamide indazoles. Further extension of this optimized (NaH in THF) protocol to various C-3, -4, -5, -6, and -7 substituted indazoles has highlighted the impact of steric and electronic effects on N-1/N-2 regioisomeric distribution. For example, employing C-7 NO2 or CO2Me substituted indazoles conferred excellent N-2 regioselectivity (≥ 96%). Importantly, we show that this optimized N-alkylation procedure tolerates a wide structural variety of alkylating reagents, including primary alkyl halide and secondary alkyl tosylate electrophiles, while maintaining a high degree of N-1 regioselectivity.
Keywords: indazole; N-alkylation; regioselective; sodium hydride; tetrahydrofuran